332 What's causing obesity in pets and what can we do about it?. (30th November 2020) - Pretlow, Robert
Abstract: The majority of dogs (56%) and cats (60%) are now overweight or obese. A novel theory posits that obesity in pets is due to "treats" and excessive meal amounts given by the "pet-parent" to obtain affection from the pet, which enables "'eating addiction" in the pet and results in pet-parent "co-dependence." The pet-parent may even become hostage to the treats/food to avoid the ire of the pet. Eating addiction in the pet appears related to stress/conflict, involving the displacement mechanism, which is a bio-behavioral mechanism in the brains of all animals, even fruit flies. It allows the animal to deal with situations that cannot readily be faced or avoided or are thwarting, such as social isolation. Displacement behavior is out-of-context, irrepressible behavior, e.g. an animal in the wild who sleeps or feeds when threatened by a predator. It is thought due to re-channeling of overflow brain energy to another drive (e.g. feeding drive) when two drives, e.g. fight or flight, equally oppose each other. Moving the opposing drives out of equilibrium, by resolving the animal's stressful life situations, theoretically halts the displacement mechanism and addictive behavior, e.g. overeating/obesity. Similarly, dealing with the pet-parent's stressful life situations curtails displacement regarding overfeeding the pet. Treatment for each contribution to companion animal obesity will be presented: Pet-parent seeking affection from the pet by giving food treats, which induces and subsequently triggers displacement overeating in the pet -- > Treatment is pet-parent withdrawal/abstinence from treat-giving. Displacement of pet-parent's stressful life situations by feeding the pet. The received affection induces and subsequently triggers further treat-giving by the pet-parent. -- > Treatment is developing an action plan for each of the pet-parent's stressful life situations. Begging, annoyance, aggression, and hostage state of the pet. -- > Treatment is "tough love" by the pet-parent.